A new species of the genus Eutyphoeus Michaelsen 1900 (Clitellata: Acanthodrilidae) from the North-Eastern Biogeographic Zone, India - Ahmed, Shakoor; Julka, Jatinder Mohan; Banerjee, Dhriti; Marimuthu, Nithyanandam (Zootaxa, 2023)
A new species of the genus Eutyphoeus is described herein from the material collected from Assam, the North-eastern region of India. The new species Eutyphoeus dhubriensis sp. nov. belongs to a group of avestibulate, metandric species, with bidiverticulate spermathecae, lacking lateral intestinal caecae. The proposed species is distinguished from its congeners by the shape, position of genital markings and associated glands, as well as number and position of ventral intestinal caecae and supra-intestinal glands.